2008
DOI: 10.2353/ajpath.2008.080272
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Overexpression and Small Interfering RNA Suppression Demonstrate That Plasminogen Activator Inhibitor-1 Produces Elevated Collagen Accumulation in Normal and Keloid Fibroblasts

Abstract: Keloids are tumor-like skin scars that grow as a result of the aberrant healing of skin injuries, with no effective treatment. We provide new evidence that both overexpression of plasminogen activator inhibitor-1 (PAI-1) and elevated collagen accumulation are intrinsic features of keloid fibroblasts and that these characteristics are causally linked. Using seven strains each of early passage normal and keloid fibroblasts, the keloid strains exhibited inherently elevated collagen accumulation and PAI-1 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 71 publications
6
31
0
Order By: Relevance
“…Such an inhibitory effect on collagen synthesis was also confirmed previously in an in vitro keloid model. 12 Despite the link between PAI-1 and apoptosis, 31 no significant changes were observed in our OC model. This could be explained by the low siRNA concentration used (250 nM).…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Such an inhibitory effect on collagen synthesis was also confirmed previously in an in vitro keloid model. 12 Despite the link between PAI-1 and apoptosis, 31 no significant changes were observed in our OC model. This could be explained by the low siRNA concentration used (250 nM).…”
Section: Discussionmentioning
confidence: 72%
“…Gene transfection using RNAi in human keloid cells either using cell culture or coculture was made possible with siRNA, 12 as well as in organotypic normal skin model. 30 However, there have been no studies to date investigating the applicability of RNAi to silence a target gene in a keloid OC model, to evaluate its efficiency as a potential antikeloid treatment in situ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is routine to compare patterns of gene expression in cultured cells at low passage number to minimize loss of an in vivo phenotype (Feghali and Wright, 1999; Smith et al , 2008; Tuan et al , 2008). It has been reported that simply culturing cells results in loss of a difference in α1β1 integrin collagen receptor expression between fibroblasts from keloids and normal skin (Szulgit et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This altered ratio of uPA to PAI-1 causes less degradation of fibrin and other ECM proteins in keloid fibroblasts and thus contributes to dermal fibrogenesis (Tuan et al, 1996). Furthermore, while adenoviral-mediated overexpression of PAI-1 in normal and keloid skin fibroblasts causes significantly elevated levels of collagen accumulation, siRNA mediated depletion of cellular PAI-1 causes a reduction in the levels of collagen, suggesting PAI-1 controls the levels of collagen, an important profibrotic marker and contributor to hypertrophic scarring (Tuan et al, 2008). …”
Section: Pathobiology Of Tissue Fibrosismentioning
confidence: 99%